Proximity Begins with a Smile, But Which One? Associating Non-duchenne Smiles with Higher Psychological Distance - Bogodistov, Yevgen; Dost, Florian (Frontiers in Psychology, 2017)
This study reveals that Duchenne (genuine) and non-Duchenne (non-genuine, polite) smiles are implicitly associated with psychological proximity and distance, respectively. These findings link two extensive research streams from human communication and psychology. Interestingly, extant construal-level theory research suggests the link may work as smiles signaling either a benign situation or politeness, resulting in conflicting predictions for the association between smile type and psychological distance. The current study uses implicit association tests to reveal theoretically and empirically consistent non-Duchenne-smile–distance and Duchenne-smile–proximity associations for all four types of psychological distance: temporal, spatial, social, and hypothetical. Practically, the results suggest several useful applications of non-Duchenne smiles in human communication contexts.